A arqueologia entre os desafios da modernidade e da contemporaneidade, - Gomes, Sérgio Alexandre (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2019)
This article discusses archaeology within the contexts of the socio-cultural project of modernity and contemporaneity ethical thought. By exploring the relationship between archaeological practice and the project of modernity, one can question whether an archaeologist is able to produce knowledge that avoids both the false promises and inevitable failures of modernity. It is argued that from the dialogue between archaeological epistemology and contemporaneity ethical thought an alternative to the modern project of knowledge of the past may emerge; an understanding that is more focussed on the irreducibility of past vestiges and a recognition of its difference. Through acknowledging the irreducible character of the material vestiges of the past, archaeology becomes a translation practice; a practice aiming to exceed the incommunicability of these vestiges. In this practice of translation, archaeologists come face to face with what is irreducible (or untranslatable); this creates the opportunity to look at the knowledge produced, to reframe that knowledge as a dialogue between their epistemology and their ethics. An epistemology which establishes a construct of rules in which knowledge is measured by its ability to demonstrate truths; and an ethical framework which, by focusing on the irreducible character of the vestiges, discusses the (im)possibilities of demonstrating the truthfulness of knowledge about the past and remembers that the purpose of archaeological knowledge is to do justice to the difference of the past. By focusing on the irreducibility or untranslatable nature of this difference, contemporary ethical thought challenges archaeology to consider the aporias of its translation practice as an integral part of its discourse; as a way of enunciating the difference of the past and as a lasting attempt to create different translation grammars.